PENGEMBANGAN MULTIMEDIA UNTUK MATERI PENDIDIKAN KARAKTER DISIPLIN PADA PELATIHAN PENDIDIK PAUD DI KECAMATAN SELAKAU KABUPATEN SAMBAS - Henniarti, Henniarti; Aunurahman, Aunurrahman; Usman, Andy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe qualifications of PAUD educators in Kabupaten Sambas are mostly still in senior secondary education or under D-2. This data shows that PAUD educators are carrying out their duties beyond their authority. With multimedia can help PAUD educators who attend the training to more easily understand the material submitted by the Instructor or trainer to improve professional competence. This research is a multimedia development research with meggunakan development stage of Borg and Gall, with the subject of research is amounted to 30 participants. Stages of multimedia development that dilakkuan Research and information collecting, planing, Develop preliminary form of product, Preliminary field testing, Main product revision, Operational field testing and Final product revision. Data were obtained through expert validation questionnaires, observations, interviews, participant response questionnaires, and documentation. Further analysis is done. The test result of the description, about 83.34% of the participants can understand the material delivered well. While 16.67% of them still do not understand this material in full. Meanwhile, the measurement of micro teaching result from 5 groups were in the range of 61 - 80 as many as 4 groups (80%) with good criteria and range of 81 - 100 as many as 1 group (20%) with very good criteria. Based on these results can be concluded that this material can be practiced by educators well. This means the goal of delivering this material is achieved.Â Key words: development, multimedia, PAUD